Characterising spatio-temporal coupling of extreme ultraviolet ultrashort pulses from high harmonic generation - Witting, T; Wyatt, A; Monmayrant, A; Walmsley, I; Haworth, C; Robinson, J; Tisch, J; Marangos, J (Optical Society of America, 2007)
This work has demonstrated a simple method to measure spatio-temporal coupling in XUV high harmonic generation via the use of spatial shearing interferometry. The method is based on a well established technique used in the visible domain which is robust to noise and can also be measured in a single shot that such a method can prove valuable in further understanding of propagation and phase-matching effects in high harmonic generation, as well as providing a tool for performing reference based time-resolved spectroscopy.